Explorations of Post Constrained Recovery Residual Stress of Shape Memory Alloys in Self-healing Applications - Haider, Muhammad Istiaque; Rezaee, Maysam; Salowitz, Nathan (Proceedings of the Wisconsin Space Conference, 2022)
Self-healing materials with intrinsic capabilities of geometric restoration and damage recovery have a tremendous potential to improve product safety and reliability, especially in space applications where recovery or manual performance of repairs may be prohibitive, dangerous, or impossible. Self-healing materials typically incorporate a complex internal structure containing constituent materials of different functionality and one of the primary methods is to reinforce self-healing materials with shape memory alloys that can be activated to restore geometry and close a fracture. Recent experimental investigation revealed that Nickel Titanium (NiTi) shape memory alloys (SMAs) could repeatedly produce stable residual stresses following constrained recovery when held in a constrained condition during temperature change through the forward and reverse transformations. The ability to produce this post constrained recovery residual stress (PCRRS) in a low temperature state, without continuous actuation, and to regenerate it repeatedly have the potential to advance self-healing capabilities and even damage prevention.